Parent participation in alcohol prevention: Evaluation of an alcohol prevention programme. Issue 6 (December 2017) - Adolfsen, Frode; Strøm, Henriette Kyrrestad; Martinussen, Monica; Handegård, Bjørn Helge; Natvig, Henrik; Eisemann, Martin; Koposov, Roman
Aim: The main purpose of this study was to evaluate the effectiveness of the parental part of the Norwegian Unge & Rus (Youth and Alcohol) programme. The intervention was aimed at changing parents' rules and attitudes towards adolescent alcohol use, and their ability to talk with their adolescents about alcohol, as well as improving parents' relationships with and knowledge about their adolescents. These topics were addressed during parent meetings at school. Method: The effectiveness of the parent programme was tested using a longitudinal quasi-experimental control group design. Parents completed four online questionnaires N = 1166 at T1 in 2011 and N = 591 at T4 in 2013. Mixed models with observations nested in individuals were used to test the difference in rates of change between the groups. Results: Parents in both groups reported strict rules and attitudes towards alcohol use. There were no significant differences in the changes between the two parent groups in terms of rules and attitudes at the three follow-up time points. The parents in the intervention did not change significantly compared to the parents in the comparison group on other alcohol-related questions. Conclusions: Parents are important facilitators for the transmission of alcohol-related attitudes and rules. However, our study did not show significant differences between changes experienced by the intervention group and those of the comparison group for the main outcome variables, such as rules, attitudes and talking about alcohol with their adolescents.